Anti-biofilm peptides as a new weapon in antimicrobial warfare. (October 2016) - Pletzer, Daniel; Coleman, Shannon R; Hancock, Robert EW
Highlights: To date no antibiotics have been specifically developed for biofilm infections. Anti-biofilm peptides directly address chronic multi-resistant bacterial infections. They demonstrate broad spectrum activity. They uniquely target the stringent stress response required for biofilm growth. They are synergistic with common antibiotics even against antibiotic resistant bacteria. Abstract : Microorganisms growing in a biofilm state are very resilient in the face of treatment by many antimicrobial agents. Biofilm infections are a significant problem in chronic and long-term infections, including those colonizing medical devices and implants. Anti-biofilm peptides represent a very promising approach to treat biofilm-related infections and have an extraordinary ability to interfere with various stages of the biofilm growth mode. Anti-biofilm peptides possess promising broad-spectrum activity in killing both Gram-positive and Gram-negative bacteria in biofilms, show strong synergy with conventional antibiotics, and act by targeting a universal stringent stress response. Understanding downstream processes at the molecular level will help to develop and design peptides with increased activity. Anti-biofilm peptides represent a novel, exciting approach to treating recalcitrant bacterial infections.